2018
DOI: 10.1039/c7cc08930a
|View full text |Cite
|
Sign up to set email alerts
|

The Janus-faced chromophore: a donor–acceptor dyad with dual performance in photon up-conversion

Abstract: An electron donor-acceptor dyad based on BODIPY (acceptor) and anthracene (donor) plays either the role of sensitizer or emitter in triplet-triplet annihilation photon up-conversion (TTA-UC). This Janus-like behavior was achieved via altering the relative ordering of charge-transfer and local excited state energies in the dyad through the polarity of TTA-UC media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…We then undertook singlet oxygen quantum yield studies of the water-soluble derivatives, BAD-13-BPyrD-19 and a control (BODIPY 20) in water (Table 3), using a protocol adopted from literature (see SI). [15] Overall, they show comparable singlet oxygen quantum yields to that of the parent BODIPYs (BAD- [5][6][7][8][9][10][11][12]. Notably, control 20 displays negligible singlet oxygen generating abilities, as expected.…”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…We then undertook singlet oxygen quantum yield studies of the water-soluble derivatives, BAD-13-BPyrD-19 and a control (BODIPY 20) in water (Table 3), using a protocol adopted from literature (see SI). [15] Overall, they show comparable singlet oxygen quantum yields to that of the parent BODIPYs (BAD- [5][6][7][8][9][10][11][12]. Notably, control 20 displays negligible singlet oxygen generating abilities, as expected.…”
Section: Methodsmentioning
confidence: 52%
“…Some of these exhibit a unique dual performance in triplet-triplet annihilation photon upconversion (TTA-UC), either as a sensitizer or emitter component. [12] We propose that these compounds have characteristics fundamental to PDT photosensitizers. Firstly, PeT is enhanced in polar media due to stabilization of the charge-separated state, providing a singlet oxygen-generating mechanism (Table 1) that can be modulated.…”
Section: Introductionmentioning
confidence: 99%
“…A unique dual performance of dyad 3 was demonstrated by Turshatov and coworkers in the following TTA-UC systems: 1) based on dyad 3 and perylene in dichloromethane (Figure 18a) and 2) based on dyad 3 and Pd(II) tetrabenzoporphyrin (Figure 18b) in toluene. 93 In dichloromethane, where intramolecular PET in 3 is thermodynamically allowed, excitation of system (1) with 525 nm light (absorption band of 3) leads to the BODIPY triplet state generation, followed by TTET to perylene and results in an anti-Stokes emission at 445 nm (perylene fluorescence) via TTA. Alternatively, in toluene 3 behaves as a typical fluorophore, exhibiting negligible ISC and high fluorescence quantum yield (0.95).…”
Section: Triplet-triplet Annihilation Upconversionmentioning
confidence: 99%
“…Recently in a proof-ofprinciple study, we demonstrated triplet sensitization switching in BADs by changing the media polarity in triplet-triplet annihilation photon up-conversion (TTA-UC). [21] Figure 3. (A) Previously studied BADs forming triplet excited states via PeT and (B) dyads studied in this work.…”
Section: Articlementioning
confidence: 99%